Persepsi Siswa Tentang Peran Guru Dalam Memotivasi Belajar Biologi Di Kelas XI SMA Negeri 1 Aek Natas - Sabarita; Fitri Endang Srimulat; Muhammad Rusli (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
Learning motivation is one of the important factors that influence students' academic success, especially in Biology learning which requires deep understanding and high learning interest. This study aims to determine students' perceptions of the role of teachers in motivating Biology learning in class XI of SMA Negeri 1 Aek Natas. The method used is a quantitative descriptive approach, and data were collected through a closed questionnaire with a Likert scale distributed to 33 students. The results showed that most students had a positive perception of the role of teachers in motivating learning, both through a conducive classroom atmosphere, innovative learning methods, and providing constructive feedback. In conclusion, teachers have a significant role in generating students' learning motivation. The implications of this study emphasize the importance of improving teacher competence in motivational aspects to create a fun and effective learning experience for students.